A REMARKABLE ASSEMBLAGE OF EARLY BARREMIAN AMMONITES IN THE CENTRAL WESTERN CARPATHIANS (BUTKOV QUARRY, SLOVAKIA) - Vašíček Z. (My University, 2006)
A remarkable fossiliferous horizon dominated by ammonites has been recorded in Lower Barremian clayey limestones of the Butkov Quarry in the Slovak Central Carpathians. The rich ammonite assemblage yielded 16 genera and 21 species. The 15 species are described in detail; four of these are new. Numerous barremitids are accompanied by biostratigraphically significant pulchelliids, some heteromorphs and particularly by representatives of the family Holcodiscidae. The composition of the ammonite assemblage, which contains only taxa belonging to the Mediterranean faunal province, is characteristic of the Early Barremian Kotetishvilia compressissima ammonite Zone.
Keywords: AMMONITES; BUTKOV QUARRY; EARLY BARREMIAN; LúčKOVSKÁ FORMATION; MANíN UNIT; Мезозой::Меловая::Нижний::Барремский; Mesozoic::Cretaceous::Lower::Barremian